"Meek-eyed moods": On John Clare's Inarticulate Images. Issue 3 (4th May 2019) - Grandy, Claire
ABSTRACT: This essay brings together two disparate discourses to consider the role of description and observation in the later work of John Clare: contemporary reading debates and the "descriptive turn, " drawing particularly on Heather Love's theory of "thin description"; and Clare's own commitment to observing and recording nature, which has led to many readings of his work premised upon decentering the poetic ego in favor of a maximalist and receptive poetics. I argue that a shared desire to move beyond prescribed interpretive frames drives both Clare's descriptive poetics and the recent "descriptive turn." I consider as well how a rhetoric of photography and photographic ways of seeing inform contemporary interpretations of these descriptive practices in a strange parataxis of nature/machine, in part through the trope of immediacy. Ultimately, I suggest that the premise of inarticulate images or "mere description" is reflexively inscribed by the work of framing itself, as a multivalent and necessary apparatus of any reading practice.